Bioactive compounds characterization of Anredera cordifolia leaf and its in silico antibacterial mechanisms against Aeromonas hydrophila - MUH. SULAIMAN DADIONO; SLAMET BUDI PRAYITNO; PURNAMA SUKARDI; DESRINA DESRINA; SARJITO SARJITO; PUTUT HAR RIYADI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dadiono MS, Prayitno SB, Sukardi P, Desrina, Sarjito, Riyadi PH. 2025. Bioactive compounds characterization of Anredera cordifolia leaf and its in silico antibacterial mechanisms against Aeromonas hydrophila. Biodiversitas 26: 3561-3570. Aeromonas hydrophila is a major pathogenic bacterium in aquaculture, causing severe disease outbreaks and significant economic losses. Due to rising antibiotic resistance, this study aimed to identify bioactive compounds from Anredera cordifolia (binahong) leaf extract and evaluate their antibacterial mechanisms against A. hydrophila through an in silico approach. The compounds were identified using UV-Vis spectrophotometry, Fourier Transform Infrared (FT-IR), and Gas Chromatography-Mass Spectrometry (GC-MS). GC-MS analysis revealed six dominant compounds: Butylated Hydroxytoluene (BHT), Hexanedioic acid bis (2-ethylhexyl) ester, Diisooctyl adipate, Dimethylpyrroline, Cyclohexane, and 1-Ethyl-1-methylcyclohexane. Among these, BHT demonstrated the strongest predicted antibacterial activity, with a Pa (probability of activity) of 0.789 and Pi (probability of inactivity) of 0.004. In silico docking analysis indicated that BHT effectively targets two key bacterial enzymes, 1-deoxy-D-xylulose-5-phosphate synthase (DXS) and Carbonic Anhydrase (CAH), suggesting interference in bacterial metabolism and survival. These findings indicate that A. cordifolia leaf extract, particularly BHT, holds promise as a natural antibacterial agent to control A. hydrophila infections in aquaculture. Further in vivo validation is recommended to confirm its therapeutic potential.